Precision Medicine Approaches in Oncology: Current Trends and Future Directions - Asrina, Andi (Advances in Healthcare Research, 2024)
Purpose: This study examines the transformative potential of precision medicine in oncology, highlighting advancements in targeted therapies and immunotherapies and addressing both practical and theoretical challenges in clinical implementation. Research Design and Methodology: This study employs a mixed-methods design, integrating quantitative data from a cross-sectional survey of oncologists with qualitative insights from in-depth interviews with key stakeholders. Advanced bioinformatics tools and multi-omics data, including genomics, proteomics, and transcriptomics, are analyzed to identify novel therapeutic targets and biomarkers. Findings and Discussion: The findings demonstrate that precision medicine enhances patient outcomes by tailoring treatments to the genetic and molecular profiles of tumors. Targeted therapies, such as tyrosine kinase and epidermal growth factor receptor inhibitors, exhibit enhanced efficacy and reduced toxicity. Immunotherapy, remarkably immune checkpoint inhibitors, demonstrates significant promise but shows variability in patient responses, underscoring the need for predictive biomarkers. Integrating multi-omics data provides a comprehensive understanding of cancer biology and new therapeutic targets. Challenges include high costs, the need for robust bioinformatics infrastructure, and ethical considerations. Implications: This study highlights the importance of investing in bioinformatics infrastructure, establishing standardized guidelines, and providing training for healthcare providers. Policymakers should develop strategies to reduce the costs of genetic testing and ensure equitable access to precision medicine. Future research should focus on cost-effective genomic testing methods, combination therapies to overcome resistance, and expanding studies to diverse populations to enhance the applicability and accessibility of precision medicine benefits.